Rhabdomyolysis in a 10-month-old child - Hui Shao; Na Wang (Medicine, 2026)
Rationale: Early diagnosis and prompt treatment of rhabdomyolysis (RM) in children are crucial to prevent potential complications, such as acute renal failure (ARF). Given that the clinical manifestations of RM in pediatric patients are often atypical, especially in infants, this case report aims to improve the recognition of RM by analyzing a specific clinical case and reviewing relevant literature. Patient concerns: A 10-month-old girl was admitted to the hospital with a 3-day history of fever and a 1-day history of cough and rash. The child had no obvious cause of fever and showed no typical symptoms of RM, such as myalgia or myoglobinuria. Diagnoses: Physical examination revealed red papules on the skin of the whole body. Laboratory tests showed a significant increase in serum creatine kinase (CK; 119,985 IU/L) and myoglobin (816.7 µg/L). The diagnosis was confirmed as RM based on these laboratory results, despite the absence of the classic clinical triad. Interventions: The patient received symptomatic and supportive treatments, including atomization with budesonide and ipratropium bromide to relieve cough, oral administration of cefaclor to resist infection, and sodium bicarbonate to alkalize urine and prevent renal damage. In addition, methylprednisolone sodium succinate was used to regulate immunity, along with hepatoprotective agents (reduced glutathione) and myocardial nutrition agents (creatine phosphate sodium). Outcomes: After 13 days of hospitalization, the patient’s symptoms (rash, cough, and thrush) disappeared. Laboratory parameters, including CK, CK isoenzyme, liver enzymes, and myoglobin, decreased significantly and returned to normal levels during follow-up. No ARF or recurrence was observed during the 6-month follow-up period. Lessons: The recognition of RM in children should be improved. Clinicians should be vigilant when encountering atypical symptoms in conjunction with substantially elevated serum CK. Early and accurate diagnosis, along with active fluid resuscitation, can effectively reduce the incidence of ARF and improve prognosis.